Review of Allied Health Education: 1 - Dulmage, Mary; Perry, J. Warren; Mase, Darrel Jay, 1905-; Hamburg, Joseph (Book collections on Project MUSE., 2015)
Allied health education has long lacked a common literature, as the activities of all these diverse disciplines have been reported only in the specialty journals of each. This review provides a locus for articles of a broad and general nature which the entire spectrum of allied health educators and students will find of vital interest. Some of the topics included in this first review include dental education, clinical laboratory work, radiologic technology, the physician's assistant, occupational therapy, and preventive health care. Additional reviews to be published on a regular basis will be devoted to other health disciplines and general health topics.